1964
DOI: 10.2466/pr0.1964.14.2.475
|View full text |Cite
|
Sign up to set email alerts
|

Saccharin Avoidance Behavior Instigated by X-Irradiation in Backward Conditioning Paradigms

Abstract: Sixty Sprague-Dawley rats were randomly assigned to eight groups of seven animals each. The remaining four animals served as a pooled control. The eight experimental groups received 68 r of x-irradiation during a 10-min. exposure period. The pooled control group received only sham-irradiation. Animals were presented a choice of tap water of 0.1% saccharin solution at delays following irradiation ranging from 0 to 96 hr. Subsequent saccharin consumption was recorded for 4 days following irradiation. Results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
8
0

Year Published

1966
1966
1985
1985

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 9 publications
2
8
0
Order By: Relevance
“…In taste aversion learning as well as in more traditional conditioning experiments, true backward conditioning does not occur, but there may be apparent backward aversion conditioning when the effects of the US are delayed (Revusky & Garcia, 1970, p. 7). If X-irradiation is administered up to about an hour before saccharin consumption, for instance, a saccharin aversion will develop (Scarborough, Whaley, & Rogers, 1964;Smith, Taylor, Morris, & Hendricks, 1965) because the prodromal X-irradiation syndrome develops gradually (Gerstner, 1960) and reaches its peak after the saccharin is consumed.…”
Section: Methodsmentioning
confidence: 99%
“…In taste aversion learning as well as in more traditional conditioning experiments, true backward conditioning does not occur, but there may be apparent backward aversion conditioning when the effects of the US are delayed (Revusky & Garcia, 1970, p. 7). If X-irradiation is administered up to about an hour before saccharin consumption, for instance, a saccharin aversion will develop (Scarborough, Whaley, & Rogers, 1964;Smith, Taylor, Morris, & Hendricks, 1965) because the prodromal X-irradiation syndrome develops gradually (Gerstner, 1960) and reaches its peak after the saccharin is consumed.…”
Section: Methodsmentioning
confidence: 99%
“…His measure of aversion was reduction in intake in a 10-min., singlebottle test, and he reported conditioned aversions for all groups with CS-US delays up to 8 hr. Nachman concluded that LiClinduced taste aversions conditioned over long CS-US delays were similar to the radiation-induced taste aversions reported by Smith and Roll. It is known that ionizing radiation is an effective US in the taste aversion problem in a "backward-conditioning" design (Mor-ris & Smith, 1964;Scarborough, Whaley, & Rogers, 1964). Morris and Smith (1964) reported conditioned aversion to saccharin resulting from a procedure in which rats were first irradiated with 100 r. and were then allowed 20-min CS access 1 hr.…”
mentioning
confidence: 99%
“…Taste aversions produced by US-CS, or " backward," procedures have also been reported, but have not yet been incorporated into the bait-shyness literature. Scarborough, Whaley, and Rogers (1964) and Morris and Smith (1964) reported conditioned aversion to saccharin solutions resulting from similar procedures in which rats were first exposed to ionizing radiation (US) and then allowed saccharin (CS) following US-CS delays of several hours. In both studies, this conditioning was attributed to the contiguous pairing of the taste CS with a prolonged adverse physiological disturbance initiated by the X-ray exposure .…”
mentioning
confidence: 99%